Gestión de las cuentas por cobrar de la unidad de Hemodiálisis Dial-Los Ríos en el periodo 2021-2022. - García Goyes, Gabriela Briguitte (2023)
Accounts receivable represent the company's legal right to collect payments from third parties for transactions that have occurred. The management of accounts receivable involves controlling the credit granted, from the moment it is approved until the collection is made according to the collection policies established by the entity. However, a deficient prior evaluation and a high volume of past due invoices can affect the collectability of the granted credits. This investigation aims to analyze the collection management procedures during the period 2021-2022 and gain a deep understanding of the processes involved. Qualitative and quantitative approaches, as well as the analytical method, were used to evaluate the management of accounts receivable of the company. The results indicate that the institution has minimally reduced the level of uncollectible accounts compared to other assets but still heavily relies on debt financing to capitalize its operations. It is necessary to evaluate the success of accounts receivable management to identify strengths and weaknesses, which will facilitate decision-making to improve the process.